Multimodel Cognitive Training to Improve Athletes’ Decision-Making Ability in Open-Skill Sports - Komarudin, Komarudin; Awwaludin, Patriana Nurmansyah; Firdaus, Ivan Rivan; Febrianty, Mona Fiametta; Novian, Geraldi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Decision-making is one of the basic skills needed by athletes to determine actions in a situation. Especially in the open-skill category of sports, where a player must be able to determine the action to be taken quickly and precisely, accompanied by unpredictable environmental conditions. This study aims to determine the effect of multimodel cognitive training on the decision-making of athletes in the open-skill category of sports. The method used in this study is an experimental method with a pretest-posttest control group design. The sample used in this study was 28 athletes in open-skill sports. Sampling was done by random selection, then divided into two groups, namely the experimental group with multimodel cognitive training and the control group with physical activity games. In measuring the level of decision-making athletes use the research instrument The Decision Style Questionnaire at the time of pre-test and post-test. Multimodel cognitive training and physical activity games have a significant effect on improving the decision-making of athletes in the open-skill category. However, Multimodel cognitive training shows better results in improving the decision-making of athletes in open-skill sports. This study concludes that multi-model cognitive training and physical activity games can improve the decision-making of athletes in the open-skill category, but multi-model cognitive training has a more significant effect.